Market Orientation Of Value Chains Based On Two Case Studies From Livestock Industry In Malaysia - Khairul Niza, Yahya (2008)
This paper extends the concept of market orientation from the firm to the value chain level and seeks to develop empirically founded propositions on determinants of different levels of market orientation of value chains. Two case studies on value chains within the areas of agribusiness are conducted. For each value chain, desk research is combined with interviews with decision-makers of all types of value chain members. Interview guidelines are derived from a conceptual model of potential determinants of value chain market orientation. Degree of market orientation of value chains is found to be related to degree of heterogeneity and dynamism of end-users served, nature of chain relationships, regulations and prevailing mental models of decision-makers. Short and balanced chains are believed to further upstream market orientation.